Muxama and other traditional food products obtained from tuna in south Portugal and Spain: review and future perspectives - Eduardo Esteves; Jaime Aníbal (Journal of Ethnic Foods, 2019)
Abstract There is evidence that consumers perceive fish as healthy (Carlucci D et.al, Appetite 84:212–27,2015; Vanhonacker F et.al, Br Food J 115:508–25,2013; Verbeke W et.al, Public Health Nutr 8:422–9,2005.). Historically, the development of (traditional) processing techniques allowed for the preservation of excess quantities of fresh fish for storage or transport. Those technologies are not well documented and are being lost with the trend to urbanization and consumption of convenience, ready-to-eat food. In the so-called developed world, there is still a considerable demand for traditionally processed (sea)food products, wherein the raw material and the final product are of high value. Muxama or mojama is a traditional, highly valued food product prepared from dry-cured tuna loins that is a delicatessen in the southern Iberian Peninsula: Algarve (Portugal) and Andalucía, Murcia, Alicante, and Valencia (Spain). The tuna (mostly Thunnus obesus and T. albacares) loins are salted and dried following a typically artisanal process that incorporates empirical knowledge passed down numerous generations since at least the tenth century Common Era (Aníbal J and Esteves E, Muxama and estupeta: traditional food products obtained from tuna loins in South Portugal and Spain, Traditional food products 2016, Lindkvist KB et.al, Can Geogr-Géogr Can 52:105–20,2008, Gallart-Jornet L et.al, La salazón de pescado, una tradición en la dieta mediterránea [The salting of fish, a tradition in the Mediterranean diet] 2005.). The production process changed little over the years but is different among locations, even supporting distinct certifications. The stability of muxama derives from the reduced water activity. Furthermore, the drying method has secondary effects on flavor, color, and nutritional value of the product. In southern Portugal and Spain, muxama is the prime food product obtained from tuna at the end of the traditional quartering of tunas, named ronqueamento in Portugal or ronqueo in Spain. Other food products obtained from tuna include Estupeta, Mormos, Rabinhos, Faceiras and Orelhas, Ventresca, Tarantela and Sangacho, Espinheta, Tripa, Bucho, and Ovas. These products result from employing different manufacturing procedures and processes. In this paper, we tentatively describe the main features of the processing stages and traditional food products obtained from tuna produced in the southern Iberian Peninsula (Portugal and Spain) and discuss the interactions of knowledge systems and transmission of traditional knowledge regarding its production.